Selection of Microbes and Conditions that Induced Bio-Cracking of Branched Hydrocarbon Squalane (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Biological oil hydrocarbons degradation is a complicated process, influenced by hydrocarbons properties, microorganisms and environmental conditions. The aim of this work was to select microbial strain, capable of degrading heavy branched hydrocarbons for further application in environment remediation and bio-cracking. Also, it was necessary to select optimal conditions (temperature, pH, concentration and etc.) for selected microbial strain degrading heavy branched hydrocarbons. Since crude oil and its products are mixtures of various hydrocarbons, at the first step of selection the ability of the strains to degrade individual hydrocarbons was investigated. Squalane was used as a test substrate. 10 microbial cultures belonging to genus Arthrobacter and obtained from culture collection of JSC “Biocentras” were used for the investigations. Gas chromatography analysis revealed that Arthrobacter sp NJ5 strain had the highest effectiveness (67%) in degradation of heavy branched oil hydrocarbon (Squalane) to shorter chain intermediates. So, Arthrobacter sp NJ5 could be applied in bio-cracking. For the application in industry, more detailed analyses are needed.